Motoboys! Perspectivas quanto à profissão, estresse e acidentes de trânsito: estudo de caso na cidade de Belo Horizonte - Carolina Riente de Andrade (2009)
In the global society, it is possible to notice the degradation of some jobs, the cost reduction, the intensification of the competitiveness and the increasing demand for outsourcing the workforce and services. In this context, a new category of workers emerge and thrive: the professional motorcyclist. Amongst the professions that are typical of the current economic paradigm, they opposes directly the mainstream concept witch values knowledge and specialization above everything else, being more and more requested by the organizations. However, they turned out to be extremely important to the society, guaranteeing, by means ofits mobility, personal and organizational demands. Since the decade of 1990, an increase tendency of diverse delivery services using motorcycles have been observed: urgent pizzas, sandwiches, periodicals, correspondences and documents with short arrival time. It is theadvent of motofrete. The motorcycles currently stand for 11% of the fleet of vehicles in Belo Horizonte and are involved in 53% of all traffic accidents, according to Company of Transport and Transit of Belo Horizonte S/A (BHTRANS). Though, in spite of having been recognized by the Ministry of the Work, by means of the Brazilian Classification of Occupation, the profession hasnt yet been regulated at the federal level. The enforcement of the labor laws in the companies and cooperatives is still shy and many workers dwell in irregularity. Ahead of this context, organizational stress became an important concern decades ago, being recognized since then as one of the most serious risk to individual psychosocial well-being. Typically, stress develops associated to the disequilibrium between the demands imposed to the worker, the limits of their own bodies and of its psychic structure. The general goal of this work is to analyze the category of the professional motorcyclist that work in the city of Belo Horizonte and to identify, from this analysis, the occurrence of stress, its distinctphases and symptoms, as well as the traffic accidents suffered or caused by them. To respond to the general goal proposed, this study: a) identify the profile of the professionals who work in Belo Horizonte by means of a survey, along with the analysis of documentary data; b)provide stress diagnosis; c) compose an inventory of the occurrences and the most frequent types of traffic accidents; and d) put side by side the quantitative data with the qualitative data, to identify possible discrepancies or similarities between them. It is an exploratoryresearch and the methodological strategy is the case study, with a qualitative and quantitative research. The data were collected by a survey with a representative sample of the Belo Horizonte motorcyclists and some interviews. The results show that 48% of the motorcyclistshave stress, predominately on resistance phase as well as the psychological symptoms. The qualitative stage was based on the expressive technique, used on psychology projective tests, with 15 motorcyclists, with or without stress. Their speeches were used as illustrations of the present study.